2020
DOI: 10.1136/bmjopen-2020-038828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological determinants of P-wave duration: cross-sectional data from the population-based CoLaus|PsyCoLaus study

Abstract: ObjectivesP-wave duration (PWD) is associated with the development of atrial arrhythmias, cardiovascular and all-cause mortality. With this study, we aimed to assess the distribution and determinants of PWD in the general population.DesignCross-sectional study using data collected between 2014 and 2016.SettingIn the population-based cohort CoLaus|PsyCoLaus, Lausanne, Switzerland, we used 12-lead ECGs to measure PWD. Potential demographic, clinical and biological determinants of PWD were collected by questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The amplitude of the T-wave decreases with age and shifts to the right, indicating an overall longer cardiac cycle, meaning a slower heart rate. Furthermore, the T- and P-wave intervals shorten with age; moreover, the absolute magnitude of the S-peak, Q-peak, and P-wave appears to diminish with age as well, which is in accordance with [ 36 , 37 ]. It is noteworthy that the amplitude of the R-peak shows no conclusive trend with age.…”
Section: Resultssupporting
confidence: 83%
“…The amplitude of the T-wave decreases with age and shifts to the right, indicating an overall longer cardiac cycle, meaning a slower heart rate. Furthermore, the T- and P-wave intervals shorten with age; moreover, the absolute magnitude of the S-peak, Q-peak, and P-wave appears to diminish with age as well, which is in accordance with [ 36 , 37 ]. It is noteworthy that the amplitude of the R-peak shows no conclusive trend with age.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, Cosgun et al’s study associated obesity with no other comorbidities to the increase in maximal values of P-wave width and the prolongation of P-wave dispersion [ 31 ]. Bocchi et al’s study also associated BMI and abdominal obesity with an increase in P-wave dispersion [ 32 ], and Seyfeli et al’s study associated obesity with an increase in P-wave dispersion [ 27 ]. Our research also found that P-wave duration and dispersion have higher values in overweight and obese people.…”
Section: Discussionmentioning
confidence: 99%
“…decrease in maximum upstroke velocities with age [20]. Thus, structural changes may underlie the well-described conduction slowing atria in elderly humans [21]. From a clinical perspective, we would not expect a relevant contribution of age-dependent prolongation in APD 90 to AF.…”
Section: Clinical Context: Agementioning
confidence: 99%